Effect of Layering and Fiber Orientation on The Tensile, Impact, and Flexural Properties of Polyester/Ramie Fiber Composites - Maghzari Zaka Ahmad; Taufik Azhary; Pelangi Eka Yuwita (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
Natural fiber-based composite materials have recently emerged as a promising alternative to synthetic materials due to their eco-friendly characteristics and ability to provide good mechanical strength. One of the natural fibers with strong potential as reinforcement is ramie fiber, which, when combined with a polyester matrix, can produce strong yet lightweight composite materials. This study was conducted to evaluate the effect of fiber orientation and the number of layers on the mechanical properties of polyester (ramie fiber) composites. The specimens were fabricated using the hand lay-up method with three variations: without fiber, two layers of unidirectional fibers, and two layers of woven fibers. The test results revealed that the woven fiber specimens achieved the highest performance in the tensile test, with a tensile strength of 33.31 MPa and an elastic modulus of 1.8 GPa. In the flexural test, this specimen also recorded the highest stress of 16.39 MPa and a flexural modulus of 58.3 MPa. The impact test showed that the woven fiber specimen had the highest energy absorption capacity of 4.97 Joules and an impact strength of 130.46. Overall, the use of woven ramie fibers significantly enhanced the tensile strength and impact toughness of the composite. Nevertheless, the effectiveness of reinforcement strongly depends on the proper arrangement and distribution of the fibers.